HCM-AF South Italy score for prediction of new-onset atrial fibrillation in patients with hypertrophic cardiomyopathy: data from a derivation and validation italian cohorts. (3rd October 2022) - Todde, G; Monda, E; Canciello, G; Lioncino, M; Lombardi, R; Rubino, M; Borrelli, F; Caiazza, M; Paoletta, D; De Simone, G; Pacileo, G; Esposito, G; et al.
Abstract: Background: Only one score for prediction of new-onset atrial fibrillation (AF) in patients with hypertrophic cardiomyopathy (HCM) has been developed in North America (HCM-AF North America score). Purpose: To develop a new score (HCM-AF South Italy score) in an Italian derivation cohort and to test the new score with that from North America, in an Italian validation cohort. Methods: A cohort of 228 patients with HCM and without history of AF, followed at referral center 1 for HCM, was used for model development. A cohort of 226 patients without history of AF, followed at referral center 2, was used for external validation. During follow-up (IQR 3–13 years, median 8 years), 59 (26%) patients developed new-onset AF. Data in the development cohort generated the HCM-AF South Italy score, a point score to predict AF probability: left atrial dimension >49 mm (+5 points), age at clinical evaluation <55 years (+2 points), the use of angiotensin-converting enzyme (ACE) or inhibitor or angiotensin receptor blocker (ARB) at initial evaluation (+2 points), low left ventricular (LV) ejection fraction (<50%) (+2 points), LV outflow tract obstruction (LVOTO) >25 mmHg (+2 points), NYHA class >1 (+1 point). Results: Patients from the validation cohort were older, had lower prevalence of HCM family history, lower systolic and diastolic blood pressure, taken fewer drugs like beta-blockers, ACE or ARB, calcium-channel blockers, and antiarrhythmic drugs and had lower LVOTO than patients from the derivation cohort, (overall p<0.05). During follow-up (IQR 1–10 years, median 5 years), 25 (11%) patients developed AF. ROC curve analysis demonstrated that HCM-AF South Italy score was superior to HCM-AF North America score (Figure). A HCM- AF South Italy score >4 identified patients at risk of AF with a sensitivity of 48%, specificity of 76%, PPV of 20% and NPV of 92%. Conclusion: Although derived and tested in little and quite different populations, the performance of the HCM-AF South Italy score was superior to that of the score developed in North America. Funding Acknowledgement: Type of funding sources: None.